Gene expression profiling of Arabidopsis thaliana chitinase genes in response to Alternaria brassicae challenge - S. RAWAT and A. GROVER*, N. CHANDRASHEKAR, S. ALI, (Indian Phytopathology, 2015)
The experiment was conducted to understand the gene expression profile of ten Arabidopsis chitinase genes upon Arabidopsis-Alternaria brassicae pathogenesis, both locally as well as systemically. At3g12500 (basic endochitinase), class I chitinase gene induced significantly in distal regions of infected plants. At3g16920 (Chitinase-like protein), member of class II chitinase induced 6 h post-inoculation both locally as well as distally. Among the four class IV, chitinase genes, At2g43590 (Chitinase family protein) displayed significant induction locally after infection. However in distal regions, At2g43570 (Putative chitinase) and At3g47540 (Chitinase-like protein) showed visible differential expression profile. Among class V genes, At4g19810 (Glycosyl hydrolase superfamily protein) was the only gene to give significant expression profile locally and also systemically. The genes expressed locally are presumed to have catalytic function to cleave Î²-1, 4-glycoside bond present in biopolymers of N-acetylglucosamine of chitin layer in fungal cell wall and can be candidate genes for imparting PAMP triggered immunity (PTI) and effector triggered immunity (ETI). The genes having significant expression profile for different time intervals upon A. brassicae challenge systemically, viz. At3g12500, At2g43590, At2g47540 and At4g19810, which are considered to be as excellent candidates of induced systemic resistance (ISR). The information obtained would be utilized for characterization of pathogen inducible chitinase promoters and development of transgenic plants for fungal resistance and can also be used to dissect transcription factors interacting with these genes in the signaling cascades.